Decision support systems and risk analysis for spatial planning - Mileu, Nelson (2021)
Risk amplification and spatial planning strategies are becoming increasingly intertwined, due to frequency and intensification of recurrent disasters, as a result of climate change. Promoted under the United Nations, the Sendai Framework for Disaster risk Reduction (2015-2030) set the priority of “investing in disaster risk reduction for resilience”, and therefore is committed with the mainstreaming of disaster risk assessment into land-use and spatial planning. In this research we present RiskOTe, a framework that aims at integrating the risk management component into municipal planning. RiskOTe is therefore a decision support system to assist spatial planning integrating the risk management components at the local level. RiskOTe tool is presented in order to explain its theoretical concepts, components (e.g., spatial database), and interface models. We use a case study to illustrate how the system operates.